Recombinant yeast for production of the pain receptor modulator nonivamide from vanillin - Muratovska, Nina; Carlquist, Magnus (Frontiers in Chemical Engineering, 2023)
We report on the development of a method based on recombinant yeast Saccharomyces cerevisiae to produce nonivamide, a capsaicinoid and potent agonist of the pain receptor TRPV1. Nonivamide was produced in a two-step batch process where yeast was i) grown aerobically on glucose and ii) used to produce nonivamide from vanillin and non-anoic acid by bioconversion. The yeast was engineered to express multiple copies of an amine transaminase from Chromobacterium violaceum (CvTA), along with an NADH-dependent alanine dehydrogenase from Bacillus subtilis (BsAlaDH) to enable efficient reductive amination of vanillin. Oxygen-limited conditions and the use of ethanol as a co-substrate to regenerate NADH were identified to favour amination over the formation of the by-products vanillic alcohol and vanillic acid. The native alcohol dehydrogenase ADH6 was deleted to further reduce the formation of vanillic alcohol. A two-enzyme system consisting of an N-acyltransferase from Capsicum annuum (CaAT), and a CoA ligase from Sphingomonas sp. Ibu-2 (IpfF) was co-expressed to produce the amide. This study provides proof of concept for yeast-based production of non-ivamide by combined transamination and amidation of vanillin.